Investigation of the Adequacy of 100 IU/Kg Unfractionated Heparin Loading Dose by Activated Clotting Time In Children With Congenital Heart Disease During Cardiac Catheterization - Nimet Cındık; Mahmut Gokdemır (Genel Tıp Dergisi)
Purpose: This study investigated whether an activated clotting time (ACT) between 200 and 300 sec could be achieved with a100 IU/kg unfractionated heparin (UHF) loading dose in patients with congenital heart disease (CHD) during pediatric cardiac catheterization. Materials and Methods: We included 264 patients aged 0-18 years with CHD undergoing cardiac catheterization between January 2022-March 2023. Data on patient characteristics, UHF doses, and ACT values were retrospectively obtained. The patients were intravenously administered 100 IU/kg UFH after sheath placement. We aimed to obtain a value between 200 and 300 sec according to the ACT measured at the 5th minute. If the measured ACT value at the 5th min was < 200 sec, additional heparin doses between 20 and 50 IU/kg were administered such that the total heparin loading dose did not exceed 150 IU/kg. Patients were divided into two groups based on whether the ACT value was below or above 200 sec. Results: Median age, weight, and ACT value at procedure were 6.41(IQR:2.01–32.21) months, 6.13(IQR:3.79-11.9) kg, and 212(IQR:190-240) sec, respectively. The ACT value of 170(64.4%) of the 264 patients was between 200-300 sec, which was considered the target value. The ACT value of 86(32.6%) of the 264 patients was below the target value and that of eight (3%) patients was above the target value. Hematoma occurred at the access site in four patients (1.5%). We did not detect retroperitoneal hematoma, other bleedings at location, or thromboembolism in any of the patients. No significant differences were observed in comparisons between age subgroups and ACT distribution, or between age subgroups and ACT subgroups (p>0.05) Conclusion: This study revealed that a 100 IU/kg UFH loading dose produced the target ACT value in 64.4% of the patients and that the UFH loading dose should be individualized according to the ACT value in the remaining patients.